2020
DOI: 10.1534/g3.120.401487
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Hypoxia-Specific Biomarkers in Salmonids Using RNA-Sequencing and Validation Using High-Throughput qPCR

Abstract: Identifying early gene expression responses to hypoxia (i.e., low dissolved oxygen) as a tool to assess the degree of exposure to this stressor is crucial for salmonids, because they are increasingly exposed to hypoxic stress due to anthropogenic habitat change, e.g., global warming, excessive nutrient loading, and persistent algal blooms. Our goal was to discover and validate gill gene expression biomarkers specific to the hypoxia response in salmonids across multi-stressor conditions. Gill tissue was collect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 95 publications
1
10
0
Order By: Relevance
“…The GWAS catalog includes C-reactive protein measurement and monocyte count. Differential expression of this gene may be related to hypoxia-stress [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…The GWAS catalog includes C-reactive protein measurement and monocyte count. Differential expression of this gene may be related to hypoxia-stress [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although sockeye salmon juveniles may not have been directly exposed to either hypoxic or thermal stressors at the time of sampling, the selected biomarkers are more highly activated under chronic than acute stresses (e.g. Jeffries et al , 2014 ; Anttila et al , 2015 ; Houde et al , 2019 ; Akbarzadeh et al , 2018 , 2020 ), and thus should reflect the stress signatures of their recent environmental experiences. For instance, the induction of hypoxia and thermal responsive genes in fish exposed to either water temperature and hypoxia stresses remains upregulated hours after returning to CTs and normal oxygen (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous validation of hypoxia biomarkers performed using a stress-challenge study in juvenile Chinook salmon ( Oncorhynchus tshawytscha ) showed that the combinations of biomarkers most strongly differentiating normoxic and hypoxic states varied between salinity environments. Hence, in this study, to identify signals of hypoxia in fish using the freshwater lake habitat, we combined seven hypoxia genes (biomarkers) that previously showed the strongest differential activity for fish exposed to hypoxic conditions in freshwater ( Akbarzadeh et al , 2020 ) with four general hypoxia biomarkers from the literature ( Houde et al , 2019 ) and applied these to the juvenile sockeye salmon samples obtained from Cultus and Chilliwack lakes ( Table 2 ). To examine thermal stress, 10 biomarkers previously validated in salmonids ( Akbarzadeh et al , 2018 ; Houde et al , 2019 ) were applied ( Table 2 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of research demonstrates that salmon are vulnerable to and influenced by low oxygen conditions, particularly in conjunction with additional stressors such as water temperature (Houde et al, 2019;Akbarzadeh et al, 2020). Shoaled hypoxic waters and elevated sea-surface temperatures cause vertical habitat compression (Bakun et al, 2015), which may increase interaction with predators, parasites, and pathogens, and possibly decrease feeding opportunities (Breitburg et al, 2018).…”
Section: Reflections On Hypoxia Salmon and Addressing Knowledge Gapsmentioning
confidence: 99%